2015
DOI: 10.1590/0034-737x201562060003
|View full text |Cite
|
Sign up to set email alerts
|

Interação entre volume de vaso e competição com plantas daninhas sobre o crescimento da soja

Abstract: Interação entre volume de vaso e competição com plantas daninhas sobre o crescimento da sojaA avaliação dos efeitos da competição das plantas daninhas sobre o crescimento da soja é efetuada por meio de ensaios em ambientes protegidos. Esses ensaios, geralmente, são feitos em recipientes (vasos) em que se testam os efeitos desejados em diferentes épocas de coleta. O tamanho (volume) dos vasos a ser escolhido depende do tipo de estudo, da espécie-teste e das variáveis que serão estudadas. Por esta razão, objetiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
2
2
0
3
Order By: Relevance
“…For DRM (Figure 2E), a reduction was observed when in competition with W. indica under irrigated conditions. Similar to the present study, Almeida et al (2015) found a smaller increment in DRM accumulation when the soybean competed with Urochloa brizantha and Bidens pilosa. It was verified that the competition from A. spinosus intensified the effects of the water restriction, with an even more severe reduction in DRM for the sunflower plants.…”
Section: Effects Of Competition and Water Deficiency On Sunflower Growthsupporting
confidence: 91%
“…For DRM (Figure 2E), a reduction was observed when in competition with W. indica under irrigated conditions. Similar to the present study, Almeida et al (2015) found a smaller increment in DRM accumulation when the soybean competed with Urochloa brizantha and Bidens pilosa. It was verified that the competition from A. spinosus intensified the effects of the water restriction, with an even more severe reduction in DRM for the sunflower plants.…”
Section: Effects Of Competition and Water Deficiency On Sunflower Growthsupporting
confidence: 91%
“…A presença de plantas infestantes resultou num decréscimo de 33% da produtividade. A soja em convivência com as plantas daninhas tem seu crescimento e desenvolvimento modificados pela interferência na captação dos recursos ambientais (ALMEIDA et al, 2015). Plantas de soja sob competição tendem a apresentar alterações morfofisiológicas, com reflexo na produtividade (VOLLMANN et al, 2010).…”
Section: Resultsunclassified
“…Chlorogenic acid, ferulic acid, catechin and p-anisic acid, all phenolic compounds, are reported as having a significant effect on the plant root system, acting on membrane stability and lignin synthesis with growth impairment of this plant organ on weeds (Carvalho et al, 2014;Cecchin et al, 2017). These results are important indicators of the allelopathic potential of cover crops, since sharp root reduction can affect the competitive capacity and the negative effect of the weed on the agricultural crop (Almeida et al, 2015). Cover crops promoted a suppressive effect on germination of the shrubby false buttonweed seeds (Table 3), especially by Cajanus cajan, Urochloa brizanha cv.…”
Section: Resultsmentioning
confidence: 99%
“…Weeds compete for different resources with agricultural crops, and the management of these plants is necessary to minimize production losses (Castro et al, 2001;Almeida et al, 2015). In the management of these plants, chemical method predominates by applying herbicides.…”
Section: Introductionmentioning
confidence: 99%